Mesa-redonda: Pesquisa Artística - Assis, Paulo de (2023)
What are the potentials, limits and characteristics of Artistic Research in the Brazilian music scene, both inside and outside academia? The use of capital letters emphasizes Artistic Research as its own legitimate methodological and epistemic field. Art and art-making have and are their own way of knowing and thinking. In Brazil, several signs point to the urgency of this discussion. But what are the defining characteristics of Artistic Research in Brazil? For this conversation, SiMN is inviting Bibiana Bragagnolo, a researcher at the forefront of this movement in Brazil, and Paulo de Assis, one of the leading names on the European scene.
FRIS
0
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music